2001
DOI: 10.1073/pnas.141221298
|View full text |Cite
|
Sign up to set email alerts
|

Communication between noncontacting macromolecules

Abstract: We present a quantitative experimental demonstration of solventmediated communication between noncontacting biopolymers. We show that changes in the activity of a solvent component brought about by a conformational change in one biopolymer can result in changes in the physical properties of a second noncontacting biopolymer present in solution. Specifically, we show that the release of protons on denaturation of a donor polymer (in this case, a four-stranded DNA tetraplex, iDNA) modulates the melting temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Oligonucletides were synthesized and purified as previously described (35,36). Concentrations were determined optically in 10 mM Na cacodylate, pH 7.0, buffer by using a Varian 300 UV͞Vis spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oligonucletides were synthesized and purified as previously described (35,36). Concentrations were determined optically in 10 mM Na cacodylate, pH 7.0, buffer by using a Varian 300 UV͞Vis spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…Temperature-dependent UV absorption measurements were conducted and analyzed as previously described by using an Aviv (Lakewood, NJ) DS14 UV͞VIS spectrophotometer equipped with a five-cell thermoelectric cell holder (35,(39)(40)(41). Unless otherwise indicated, oligonucleotide concentrations were always 1 M in single strand or duplex.…”
Section: Methodsmentioning
confidence: 99%
“…Proton release/uptake may be so high that the i-motif structure may be used as a proton donor/acceptor. 29 The telomeric repeat (CCCTAA) 4 can form the i-motif; its halfdissociation temperature (T m ) is 39 • C at pH 6 but is only 20 • C at neutral pH. 30…”
Section: Structural Polymorphismmentioning
confidence: 99%
“…We previously have suggested that biological processes may lead to localized changes in pH that can stabilize pH-dependent DNA structures such as the i-DNA. 56 The energetic and environment-dependent differences for i-DNA/G-quartet structures relative to duplex DNA may allow for selective control of these structures, which might potentially form transiently during critical regulatory events. The thermodynamic estimates given here suggest that the cost of replacing a conventional Watson-Crick duplex domain with a combination of i-DNA and G-quadruplex structures is energetically reasonable.…”
Section: Potential Biological Relevance Of the I-dna Motifmentioning
confidence: 99%
“…We previously used DSC to detect and characterize coupled conformational transitions in i-DNA and poly rA, a coupling that resulted in communication between noncontacting nucleic acid species. 56,57 In this study, we focus on characterizing the energetics of tetraplex formation for the prototype d(TC 5 ) oligomer, which was the first oligonucleotide shown to adopt the i-DNA structure. We also characterize the related oligomer d[(C 5 T 3 ) 3 C 5 ] in which the four d(TC 5 ) strands are linked together by three all-thymine loops to form an intramolecular rather than intermolecular tetraplex.…”
mentioning
confidence: 99%